Examining International Students’ Perspectives on Choosing the Music and Dance Program at Rajapark Institute - Compee, Thitaree; Xi, Yue; Liu, Yang; Li, Ming (Arts of Management Journal, 2025)
This study aimed to (1) investigate the academic structure and pedagogical strategies of the Music and Dance program at Rajapark Institute, (2) the experiences and challenges faced by international students in a cross-cultural educational environment, and (3) the extent to which the curriculum aligns with students’ career development goals in the performing arts sector. The participants included three faculty members, three administrative staff, and ten prospective international students, selected through purposive sampling. Data were collected using semi-structured interviews in Thai or Chinese and translated into English. Descriptive statistics and content analysis analyzed approximately 120,000 words of qualitative data. Computational techniques, including word frequency analysis, keyword network analysis, and sentiment analysis, were employed to deepen the interpretation of findings. The results indicate that the program emphasizes academic excellence, cultural integration, and career preparedness through interdisciplinary teaching and research-led pedagogy. International students expressed enthusiasm for cultural learning but encountered challenges such as language barriers, academic adaptation, and uncertainties about professional transitions. Although the curriculum provides solid foundational training, there is a need for stronger industry linkages, internship placements, and professional mentorship to bridge the education-to-employment gap. The discussion highlights the importance of integrating interdisciplinary content, enhancing support systems for international students, and aligning the curriculum with labor market demands. Moreover, the study underscores the value of technological innovation and intercultural collaboration in performing arts education. In conclusion, the Music and Dance program at Rajapark Institute holds considerable promise in delivering cross-cultural, career-oriented education. However, continued improvements in curriculum design, cultural support, and career alignment are essential for maximizing its impact. The findings offer practical implications for institutional policy and contribute to the broader discourse on international performing arts education.